KEDUDUKAN PT. PERTAMINA DALAM MELAKUKAN PERJANJIAN KERJASAMA DENGAN MITRA USAHA SPBU - Basudewa Amijaya, Anom; Oka Parwata, A. A. Gede (Kertha Semaya : Journal Ilmu Hukum, 2014)
This article discusses the position of Limited Company. Pertamina in conductingbusiness contract with its partner candidates (gas station agents). The contract offered byLimited CompanyPertamina to its partner candidates is in the form of standard contractthat creates an unbalanced condition because the partner candidates do not have abargaining position. The problems encountered here are : what are the forms of contractoffered by Limited CompanyPertamina to its partner candidates? How is the position ofLimited CompanyPertamina in theexecution of the contracts ? The research methodemployed is normative-juristic research which is based on the absence of norms or lawprinciples.The research results show that the contracts offered by Limited CompanyPertaminaare in forms of Gas Stations COCO (Company Owned Company Operated), Gas StationsCODO (company owned dealer operated), and Gas Stations DODO (dealer owned anddealer operated). The position of Limited Company Pertamina in the contract to managingthe gas stations (SPBU) is as a State-owned Company, which acts as a private lawinstitution and is obliged to undergo good corporate governance principles or goodcompany management.
Keywords: Limited CompanyPertamina, Gas stations, Business Contract, and Business Partners